2018
DOI: 10.1186/s12943-018-0803-3
|View full text |Cite
|
Sign up to set email alerts
|

PTEN/PTENP1: ‘Regulating the regulator of RTK-dependent PI3K/Akt signalling’, new targets for cancer therapy

Abstract: Regulation of the PI-3 kinase (PI3K)/Akt signalling pathway is essential for maintaining the integrity of fundamental cellular processes, cell growth, survival, death and metabolism, and dysregulation of this pathway is implicated in the development and progression of cancers. Receptor tyrosine kinases (RTKs) are major upstream regulators of PI3K/Akt signalling. The phosphatase and tensin homologue (PTEN), a well characterised tumour suppressor, is a prime antagonist of PI3K and therefore a negative regulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
168
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(171 citation statements)
references
References 161 publications
(206 reference statements)
3
168
0
Order By: Relevance
“…In this study, we found that a new Akt inhibitory agent, CTT, induced significant decreases in cell proliferation and suppressed the migration and invasion of bladder cells. In addition, we found that the expression level of PTEN increased after CTT treatment, which indicated that PTEN was a key modulator of the induction of PI3K/Akt signalling [24]. Inhibition of PTEN expression reversed the inhibitory effects of CTT.…”
Section: Discussionmentioning
confidence: 76%
“…In this study, we found that a new Akt inhibitory agent, CTT, induced significant decreases in cell proliferation and suppressed the migration and invasion of bladder cells. In addition, we found that the expression level of PTEN increased after CTT treatment, which indicated that PTEN was a key modulator of the induction of PI3K/Akt signalling [24]. Inhibition of PTEN expression reversed the inhibitory effects of CTT.…”
Section: Discussionmentioning
confidence: 76%
“…There are several potential binding sites of miR-21 on the PTEN 3'UTR, such as GAUAAG and UCUG*UG*GCUA (43,44). PTEN is an inhibitor of the PI3K/Akt signaling pathway (45), and the PTEN/Akt axis is a pivotal regulatory pathway in IR-induced cell apoptosis. He et al demonstrated that overexpression of circVRK1 could reverse the radioresistance of esophageal squamous carcinoma cells by regulating the miR-624-3p/PTEN/PI3K/Akt signaling pathway (40).…”
Section: Discussionmentioning
confidence: 99%
“…In PTEN knock-in mice harboring two cancer-associated PTEN mutations, PTENC124S and PTENG129E inhibit the PTEN lipid-phosphatase activity in a dominant negative manner, leading to increased activity of PI3K signaling and tumorigenesis [20]. Moreover, in PTEN-deficient cancer, the main carcinogenic driving force is the overactivation of AKT caused by the loss of PTEN lipid phosphatase function [20,25].…”
Section: Loss or Inactivation Of Ptenmentioning
confidence: 99%
“…NVP BEZ235 (dactolisib) is a dual PI3K/mTOR inhibitor and is currently in Phase I/II clinical trials. It is an imidazo [4,5-c] quinoline derivative compound that binds to the ATP-binding cleft of PI3K and mTOR kinase, inhibiting their catalytic activities [25]. BEZ235 exhibited satisfactory anticancer effects in preclinical studies in several types of cancer, including the following: triple-negative breast cancer, lung cancer, melanoma, colorectal cancer, renal cancer, prostate cancer, lymphoma, and mucinous adenocarcinoma of the ovary [73][74][75][76][77][78][79][80][81][82][83][84][85].…”
Section: Dual Pi3k/mtor Inhibitors Nvp-bez235 (Dactolisib)mentioning
confidence: 99%